Navigating Challenging Left Ventricular Lead Placements for Cardiac Resynchronization Therapy - Pothineni, Naga Venkata K. (J Innov Card Rhythm Manag, 2020)
Cardiac resynchronization therapy (CRT) is a mainstay in the management of heart failure patients with electrical dyssynchrony. Left ventricular (LV) lead positioning remains an important variable that predicts the response to CRT. Anatomical and technical challenges can hinder optimal LV lead placement using traditional lead implantation approaches. Knowledge of normal anatomical variants and common anomalies is essential for successful LV lead implants. With advancements in tools and techniques for LV lead delivery, the implanting electrophysiologist can target the optimal LV pacing site, rather than accepting a suboptimal location that is less likely to provide clinical benefit. In this review, we discuss various challenges to achieving optimal LV lead implantation and present strategies to overcome them.